Predicting the Image of Turkey and the Prime Minister Erdoğan Through Content Analysis of National News Media Coverage of Davos Incident - Elif Engin; Güler Şener (Selçuk İletişim)
Using content analysis of four national newspapers in Turkey and applying framing analysis, this study examines how the selected newspapers framed the image of Turkish Prime Minister Erdoğan and national image of Turkey after the Davos incident in World Economic Forum 2009. The analysis showed that the newspapers differ in their portrayal of the incident and in their construction of the image of Prime Minister Erdoğan and Turkey. Newspapers in the republican-laic side of the political spectrum in Turkey assessed the incident in negative terms and reflected a more negative image for both Prime Minister Erdoğan and Turkey, whereas newspapers with a conservative-democrat line portrayed more positive images.